P467 Nutrition audit- are we losing the plot?. (June 2019) - Stefkova, Katarina; Cummins, David; Walker, Alison
Abstract : Background and aims: Growth measurement and documentation is an essential part of practice in neonatology, as regular measuring of growth parameters leads to early recognition of possible poor growth. This means action can be taken promptly, reducing long term morbidity and mortality. The Royal College of Paediatrics and Child Health have produced guidelines on growth measurement, with NICU in RJMH having additional guidelines specific to the unit. Our aim was to audit the compliance with the guidelines in RJMH, and to find ways of improving practice. Methods: We have audited growth charts on BadgerNet of 58 babies, which was the total number of inpatient babies during the month of November. This was done as a retrospective audit. Results: 100% of babies audited had birth weight plotted on a correct chart with EDD marked on the chart. We attributed this to the fact that RJMH uses BadgerNet, which is an electronic system that automatically generates a growth chart and plots the birth weight. Birth head circumference was plotted on 69% of the babies. Out of the babies that resided in the unit over 2 weeks, 90% had a second weight noted by 2 weeks, and 72% had repeat head circumference noted within 2 weeks. Only 28% of babies had their weight plotted twice weekly thereafter, and 22% of babies had weekly head circumference plotted. Conclusions: Our conclusion from the audit is that initial growth parameters are performed well, however ongoing growth measurement and growth chart plotting requires improvement.